The ALMA-ATOMS Survey: Exploring Protostellar Outflows in HC3N - Ariful Hoque; Tapas Baug; Lokesh K. Dewangan; Mika Juvela; Anandmayee Tej; Paul F. Goldsmith; Pablo García; Amelia M. Stutz; Tie Liu; Chang Won Lee; Fengwei Xu; Patricio Sanhueza; et al. (The Astrophysical Journal)
We present the first systematic study of bipolar outflows using HC _3 N as a tracer in a sample of 146 massive star-forming regions from the Atacama Large Millimeter/submillimeter Array Three-millimeter Observations of Massive Star-forming Regions (ATOMS) survey. Protostellar outflows arise at the initial stage of star formation as a consequence of active accretion. In general, these outflows play a pivotal role in regulating the star formation processes by injecting energetic material in the parent molecular clouds. In this process, lower velocity components of outflows contain a significant portion of the energy. However, extraction of these components is difficult because the corresponding gas is often mixed with that of the ambient cloud. In our sample, we identified 44 bipolar outflows and one explosive outflow in HC _3 N ( J = 11–10). The host clumps of these outflows are found to be at different evolutionary stages, suggesting that outflows in HC _3 N are detectable in different stages of star formation. In addition, the noncorrelation of HC _3 N outflows with clump evolutionary stages suggests that HC _3 N is an unbiased tracer of outflows. Analyses revealed that HC _3 N performs slightly better in detecting low-velocity components of outflows than traditionally employed tracers such as SiO. The derived outflow parameters (i.e., outflow mass, momentum, and energy) show moderate correlations with clump mass and luminosity. Our analysis of outflow opening angles and position–velocity diagrams across the outflow lobes show that, HC _3 N is not only a good tracer of low-velocity outflows but can also detect high-velocity collimated outflows. Overall, this study indicates that HC _3 N can be used as a complementary outflow tracer along with the traditionally known outflow tracers, particularly in the detection of the low-velocity components of outflows.